Design, installation and cost evaluation of a drip irrigation system for orchards - Gato, Shirley Arizala; Murty, V.V.N.; Loof, Rainer; Mizutani, Masakazu; French Government (Bangkok : Asian Institute of Technology, 1988)
Drip irrigation system is a method of applying small amount of water into the soil through the network plastic tubes. A typical drip system for orchards Ras designed, installed and evaluated within the campus of the Asian Institute of Technology, Bangkok. The performance characteristics of the microtube as emitter Here evaluated. A computer program was developed to determine the most economical design and was compared Kith the typical design. In addition, tests comparing the use of a locally available handpump and an engine driven pump in operating the system Reconducted. The relationship between the pressure head, the length, and the diameter to the discharge of the microtube under the partially turbulent and unstable flow regime was established. An increase in temperature has no significant effect on the rate of flow under the partially turbulent flow regime. However, under the unstable condition an increase of 7oc would result to 4% increase in discharge. A slight increase in discharge was observed by bending the microtube. The optimum design shows to be superior in terms of irrigation system cost and in pumping- energy requirements. And, a locally available hand pump could satisfy the power requirements of most or the small farms, requiring a horsepower rating of 0. 02.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Irrigation; Fruit-culture